2016
DOI: 10.2174/1567202613666160902102007
|View full text |Cite
|
Sign up to set email alerts
|

Selective Modulator of Cannabinoid Receptor Type 2 Reduces Memory Impairment and Infarct Size During Cerebral Hypoperfusion and Vascular Dementia

Abstract: Vascular dementia is the highly devastating neurodegenerative disorder after Alzheimer's disease (AD) and mainly found in aged people but the effectual therapeutic target is still not there. Chronic cerebral hypoperfusion (CCH) has been broadly found in vascular dementia (VaD) patients. CCH is thought to link with neurodegenerative disorders and their subsequent cognitive deteriorate on. This study has been framed to examine the role of a selective agonist of cannabinoid receptor type 2(CB2); 1-phenylisatin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Previous studies in primary rat cell cultures have reported that activation of CB 2 R can obviously inhibit the LPS-induced transition of microglia to the Ml phenotype and thereby prevent M1-mediated inflammatory responses [ 37 ]. Further, in an animal model of VD, the selective activation of CB 2 R improves memory deficit and infarct size in chronic brain hypoperfusion [ 38 ]. In support of these reports, our findings demonstrated that in the VD model rats which received either PF or a specific pharmacological CB 2 R agonist HU308, hippocampal CB 2 R mRNA and protein expression levels in 4-VO rats at the recovery stage of ischemia were further increased compared with that in the untreated 4-VO group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in primary rat cell cultures have reported that activation of CB 2 R can obviously inhibit the LPS-induced transition of microglia to the Ml phenotype and thereby prevent M1-mediated inflammatory responses [ 37 ]. Further, in an animal model of VD, the selective activation of CB 2 R improves memory deficit and infarct size in chronic brain hypoperfusion [ 38 ]. In support of these reports, our findings demonstrated that in the VD model rats which received either PF or a specific pharmacological CB 2 R agonist HU308, hippocampal CB 2 R mRNA and protein expression levels in 4-VO rats at the recovery stage of ischemia were further increased compared with that in the untreated 4-VO group.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of TWK10-fermented soymilk extract also increases the scavenging activity of α,α-diphenyl-βpicrylhydrazyl (DPPH) and the activity levels of CAT, GSH, and SOD [33]. Additionally, 1-phenylisatin, a selective cannabinoid receptor type 2 (CB2R) agonist, has the same effects as those of TWK10-fermented soymilk extract in CCH-induced VaD rats [34]. Edaravone is a novel free radical scavenger that ameliorates neuronal damage and exerts neuroprotective effects in neurodegenerative diseases [35,36].…”
Section: Promotion Of Free Radical Scavengingmentioning
confidence: 98%
“…Collectively, these studies provide emerging evidence supporting an important role for the ECS – NO • signalling axis in controlling the physiological actions and/or viability of key cellular components of the CNS (i.e. neurons, astrocytes, microglia, brain microvascular endothelial cells), thereby impacting on cognitive and neuroendocrine function, as well as implicating the ECS – NO • pathway as a potential therapeutic target to alleviate neurodegeneration in response to brain injury and neurological conditions such as Parkinson's disease, vascular dementia, and Alzheimer's disease (Koppel et al, 2014; Aso et al, 2016; Austin and Katusic, 2016; Gomez-Galvez et al, 2016; Jayant and Sharma, 2016). …”
Section: Ecs–no• Crosstalk In Disease Development and Treatmentmentioning
confidence: 99%